2015
DOI: 10.5415/apallergy.2015.5.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough: an Asian perspective. Part 1: Epidemiology

Abstract: Asia is one of the most diverse and dynamic continents. Due to recent rapid industrialisation and urbanisation, morbidity patterns are likely to be diverse in Asian populations. Chronic cough is a disease condition resulting from host-environmental interactions, and is associated with a high global epidemiological burden. However, the underlying epidemiology remains unclear, particularly in Asia. We performed a literature search to identify peer-reviewed articles on chronic cough in community-based adult Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 67 publications
0
24
0
3
Order By: Relevance
“…Other comorbid conditions were determined by the questions on self-reported physician diagnosis of the following type “Have you ever been diagnosed with (a specific disease) by physician?” We selected following conditions on the basis of previous reports on the relationships with chronic cough; asthma, pulmonary TB, allergic rhinitis, diabetes mellitus, and depression. [2325] …”
Section: Methodsmentioning
confidence: 99%
“…Other comorbid conditions were determined by the questions on self-reported physician diagnosis of the following type “Have you ever been diagnosed with (a specific disease) by physician?” We selected following conditions on the basis of previous reports on the relationships with chronic cough; asthma, pulmonary TB, allergic rhinitis, diabetes mellitus, and depression. [2325] …”
Section: Methodsmentioning
confidence: 99%
“…Batuk kronis menjadi perhatian utama di negara berkembang, sebagai tanda gangguan saluran pernafasaan, seperti tuberkolosis paru (TB). Gejala batuk terus menerus yang berlangsung selama 2-3 minggu dapat diduga sebagai indikasi penyakit TB di beberapa negara Asia Tenggara (Song et al, 2015).…”
Section: Kata Kunciunclassified
“…Upper airway cough syndrome, also called postnasal drip syndrome or rhinitis/rhinosinusitis-related cough, also has a variable but relatively high prevalence [23]. In our recent review of Asian studies, infectious diseases such as pulmonary tuberculosis and paragonimiasis were identified as important causes of chronic cough in several South and Southeast Asian countries [24]. While the geographic differences reported in the literature may partly result from methodological heterogeneities among studies, they also suggest the necessity to tailor diagnostic pathways to the relevant geographical or ethnic population.…”
Section: Introductionmentioning
confidence: 99%